Excellent rate capability supercapacitor based on a free-standing PEDOT:PSS film enabled by the hydrothermal method. Issue 33 (5th April 2022) - Su, Zhen; Jin, Yingzhi; Xiao, Yunchao; Zheng, Haolan; Yang, Zanzhong; Wang, Hao; Li, Zaifang
Abstract : The free-standing PEDOT:PSS film is fabricated by the hydrothermal method. The film shows a rectangle characteristic and a high capacitance at the ultrahigh scan rate of 1300 mV s −1, attributed to the synergistic effect of temperature and pressure. Abstract : For the first time, herein, the hydrothermal method with H2 SO4 as the solvent is introduced to enhance the rate capability of free-standing pristine PEDOT:PSS films. The film with a record conductivity of 3188 S cm −1 displays a rectangular characteristic at an ultrahigh scan rate of 1300 mV s −1 and a stable specific capacitance of 110 F cm −3 from 0.1 to 100 A cm −3, with a capacitance retention of up to 94.8%. The flexible supercapacitor based on the films delivers a comparable energy density of 2.96 mW h cm −3 even at a high power density of 36 685 mW cm −3 . This study provides an effective method to prepare PEDOT:PSS films with outstanding electrochemical properties and potentially expand its applications in flexible devices.